MOTIVASI BELAJAR MAHASISWA DENGAN PENERAPAN MODEL PEMBELAJARAN MOBILE LEARNING DI MASA PENCEGAHAN PENYEBARAN COVID-19 - Liza Efriyanti, liza (Jurnal Abdimas ADPI Sains dan Teknologi, 2020)
One of the prevention and spread of Covid-19 is to carry out physical distancing. Physical distancing is keeping a minimum distance from one person to another, and staying away from crowd points, because if this is not done, the spread of covid-19 will be very fast, the number of patients in the hospital will explode so that health facilities will be overwhelmed to handle it. Lectures conducted online will break the chain of the spread of covid-19. The purpose of this study is to look at student learning motivation in artificial intelligence courses in the odd semester of TA. 2019/2020 by applying the mobile learning model for one semester, whether there is an increase or a decrease. The method used in the research was to spread closed questionnaires to all students who took artificial intelligence courses at the PTIK FTIK IAIN Bukittinggi Study Program, then the questionnaires were analyzed. The mobile learning model is one of the alternative learning models during this pandemic. The results showed that the mobile learning model increased student learning motivation, independent learning, more active and effective communication between fellow students and also between students and their lecturers. On average, student learning motivation, especially in the artificial intelligence course, is at a value of 8.13%, which means it is included in the good criteria of the 42 questionnaire items filled by students. The learning motivation of female students was higher (mean rank: 157.15) than boys (mean rank: 104.35).